2010
DOI: 10.1038/npre.2009.3926
|View full text |Cite
|
Sign up to set email alerts
|

Closed bioregenerative life support systems: Applicability to hot deserts

Abstract: Water scarcity in hot deserts, which cover about one-fifth of the Earth's land area, along with rapid expansion of hot deserts into arable lands is one of the key global environmental problems.As hot deserts are extreme habitats characterized by the availability of solar energy with a nearly complete absence of organic life and water, space technology achievements in designing closed ecological systems may be applicable to the design of sustainable settlements in the deserts. This review discusses the key spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…It has even been suggested that CELSS technology such as MELiSSA may assist in reclaiming hot desert regions to counter rapid desertification for productive arable farming using closed resource cycles [ 101 ]. Such regions offer high intensity PAR (productivity increases linearly with photo intensity until saturation at 2.5L 0 ), high temperature (by 30% from 17 °C to 23 °C) and high atmospheric CO 2 levels (by 30–40% at 800 ppm) to enhance arable productivity.…”
Section: Discussionmentioning
confidence: 99%
“…It has even been suggested that CELSS technology such as MELiSSA may assist in reclaiming hot desert regions to counter rapid desertification for productive arable farming using closed resource cycles [ 101 ]. Such regions offer high intensity PAR (productivity increases linearly with photo intensity until saturation at 2.5L 0 ), high temperature (by 30% from 17 °C to 23 °C) and high atmospheric CO 2 levels (by 30–40% at 800 ppm) to enhance arable productivity.…”
Section: Discussionmentioning
confidence: 99%
“…(Here we reproduce the arguments of Polyakov [13]). Let us perform an infinitesimal rotation around X 0 towards, say, X 1 : X D !…”
Section: Appendixmentioning
confidence: 95%
“…Conforme o trabalho de Polyakov e Makorova (16) , bolhas de CO que são originadas no interior do banho metálico promovem o fenômeno de ejeção das gotas.…”
Section: Formação De Poeiras Durante a Fabricação Do Açounclassified
“…O teor de carbono no metal líquido influencia na geração da PAE, estudos mostraram que a ejeção das gotas foi predominante nos momentos em que existe mais carbono e pouca escória (estágio inicial do sopro no conversor). Além disso, a vaporização de elementos com baixo ponto de ebulição atua como um segundo mecanismo de formação da PAE, sendo que este ocorre principalmente no último estágio do sopro (16) .…”
Section: Formação De Poeiras Durante a Fabricação Do Açounclassified